If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -8) + -1(6x + -6) = 0 Reorder the terms: (-8 + X) + -1(6x + -6) = 0 Remove parenthesis around (-8 + X) -8 + X + -1(6x + -6) = 0 Reorder the terms: -8 + X + -1(-6 + 6x) = 0 -8 + X + (-6 * -1 + 6x * -1) = 0 -8 + X + (6 + -6x) = 0 Reorder the terms: -8 + 6 + X + -6x = 0 Combine like terms: -8 + 6 = -2 -2 + X + -6x = 0 Solving -2 + X + -6x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + X + 2 + -6x = 0 + 2 Reorder the terms: -2 + 2 + X + -6x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + X + -6x = 0 + 2 X + -6x = 0 + 2 Combine like terms: 0 + 2 = 2 X + -6x = 2 Add '6x' to each side of the equation. X + -6x + 6x = 2 + 6x Combine like terms: -6x + 6x = 0 X + 0 = 2 + 6x X = 2 + 6x Simplifying X = 2 + 6x
| 2(3x-8)=4x+12 | | a+94-17=218 | | x+(x*.12)=95000 | | 150000+20*x=250000+11x | | 6n-3=-9+6n | | 11y-14=41 | | 26(a-28)=234 | | v/2+3=17 | | 15=-3x-6 | | (0.02)2= | | 2.5x+15=5.75x+34.5 | | (2x-3)2-4=50 | | y=-2x+12-17 | | X-8-6x-6= | | 16[x-1]=12x+36 | | (2y+5)+y=22 | | m+7.3=5 | | 6(2x-7)+4=28 | | (2x-3)(5x+4)= | | 2.7=8.37 | | 6(2x-7)+4=28answer | | (2/3x)=30 | | 7-4x=65 | | p=20h-120 | | 5a+4(3a-8)=13a | | 6m+5(m-6)=2m-5 | | 8x-15=3x+4+7x-7 | | (8t-6)(8t+6)= | | m=7.3-5 | | 14=8d-2 | | -7-3n=8+2n | | 5f+2=22 |